Poor and non-poor in the Brazilian labor market - Sônia Rocha (Institute for Applied Economic Research (ipea), 2015)
Time and locally specific poverty lines for Brazilian metropolitan areas, which concentrate a third of the country's population, are used for examining the proportion of poor along the short-term cycles, typical of the economic evolution in the 80's. Although the sensibility of poverty to the cycle is high, its long-term effect was neutral in terms of incidente of poverty from the income point of view, but clearly adverse when labor market indicators were considered. National Household Sampling Survey data combined with poverty lines allowed for the construction of labor indicators both for poor and non-poor subpopulations, which are clues to understanding income earning strategies under changing economic and demographic conditions.
Keywords: 330